Heterogeneous catalysis in 4-nitrophenol degradation and antioxidant activities of silver nanoparticles embedded in Tapioca starch - Kalantari, Katayoon; Afifi, Amalina Muhammad; Bayat, Saadi; Shameli, Kamyar; Yousefi, Samira; Mokhtar, Norrashidah; Kalantari, Alireza (Elsevier, 2019)
In this study, a simple, green and eco-friendly method was used for the synthesis of silver nanoparticles (Ag-NPs) in alkaline treated Tapioca starch. The XRD results indicated that Ag-NPs were produced after stirring for several hours at 80 °C. TEM image showed the Ag-NPs were in spherical shape with average size of 11 nm. The UV–vis results revealed clearly the formation of Ag-NPs in the range from 410 to 420 nm. Moreover, the prepared nanoparticles showed good catalytic activity in the reduction of 4-nitrophenol (4-NP). The results confirmed the catalytic activity of them in the short induction period, and the completion reaction continued within 15 min. The finding revealed also significant shift in the DPPH radical scavenging ability for studied samples. The recorded scavenging ability for the lowest concentration of the synthesized Ag-NP (50 μg/ml) was 17.29 ± 0.06 and this scavenging ability was increased to 78.60 ± 0.05, when concentration was increased to 250 μg/ml. Silver nanoparticles have many catalytic and antioxidant activities in environmental and biomedical fields. © 2016 The Authors